2019
DOI: 10.1108/jmtm-05-2018-0156
|View full text |Cite
|
Sign up to set email alerts
|

Original equipment manufacturer (OEM)-supplier integration to prepare for production ramp-up

Abstract: Purpose Although prior research provides evidence that production ramp-up is often disrupted by supplier-related problems, it fails to discuss how the original equipment manufacturer (OEM) and various types of suppliers integrate their functions and operations to secure preparations for production ramp-up. The purpose of this paper is to investigate OEM–supplier integration in a new product development (NPD) project to prepare for production ramp-up. Design/methodology/approach The results presented in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 75 publications
1
29
0
Order By: Relevance
“…The firms' main intention is to utilise the suppliers' specialised knowledge in their know-how projects to reduce time to market (Aloini et al, 2015) and increase the frequency of new products to market (Rosell & Lakemond, 2012). Manufacturers often move beyond just acquisition and sharing supplier knowledge towards integration with redesign and improvement of existing processes (António Carrizo Moreira & Ferreira, 2018;Calvi et al, 2018;Pihlajamaa et al, 2017;Wlazlak et al, 2019) or early engagement in new product development (Chesbrough, 2010;Laursen & Andersen, 2016;Rosell & Lakemond, 2012). These practices have been examined in relations with supplier integration, which enhances the speed to markets and the rate of innovation (Cavusgil et al, 2003;Ritala et al, 2015).…”
Section: Supplier Knowledge Development (Skd) Quality (Qp) and Innovmentioning
confidence: 99%
See 2 more Smart Citations
“…The firms' main intention is to utilise the suppliers' specialised knowledge in their know-how projects to reduce time to market (Aloini et al, 2015) and increase the frequency of new products to market (Rosell & Lakemond, 2012). Manufacturers often move beyond just acquisition and sharing supplier knowledge towards integration with redesign and improvement of existing processes (António Carrizo Moreira & Ferreira, 2018;Calvi et al, 2018;Pihlajamaa et al, 2017;Wlazlak et al, 2019) or early engagement in new product development (Chesbrough, 2010;Laursen & Andersen, 2016;Rosell & Lakemond, 2012). These practices have been examined in relations with supplier integration, which enhances the speed to markets and the rate of innovation (Cavusgil et al, 2003;Ritala et al, 2015).…”
Section: Supplier Knowledge Development (Skd) Quality (Qp) and Innovmentioning
confidence: 99%
“…Several studies have found that supplier collaboration is positively related to innovation in the buying firm (Liu & Li, 2017;Un et al, 2010). Communication facilitates the integration of the suppliers on the development team (Pihlajamaa et al, 2017;Wang et al, 2015;Wlazlak et al, 2019) and provides good conditions for knowledge integration. The suppliers' network closure and access to diverse information can enhance synchronously both stylistic and process innovation (Delbufalo, 2015).…”
Section: Supplier Communication (Sco) and Skdmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as a result of the slow transformation for some old enterprises, like MOTOROLA, who was once a highly qualified mobile phone manufacturer, or the need for national strategic development, many new manufacturers and suppliers have emerged as the times require, such as COMAC, China's manufacturer of big passenger aircraft. Lots of new relationships between manufacturers and suppliers in the R&D of some complex products are established thereby [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the problems were unpredicted in advance by the young manufacturer COMAC and its suppliers before they signed the collaboration, even though some of the suppliers are experienced. Due to the complexity of complex products, the problems arising in the R&D of complex products are more complicated and diverse than those of ordinary products [9][10][11][12]. Thus, the probability of the unpredicted problems is much higher.…”
Section: Introductionmentioning
confidence: 99%